2023
DOI: 10.1186/s13011-023-00523-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of post-discharge engagement for emergency department patients with opioid use history who received telehealth recovery coaching services

Abstract: Background In recent years, emergency departments (EDs) across the nation have implemented peer recovery coach (PRC) services to support patients who use opioids. The majority of such interventions discussed in the literature follow an in-person modality where PRCs engage patients directly at the ED bedside. However, the use of telehealth services in EDs is becoming more popular. These services connect PRCs with ED patients in real-time via secure communications technology, and very little is k… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…These results contribute to the growing body of evidence related to the effectiveness of ED-based PRSS interventions for OUD, with most prior research of similar interventions focusing on relatively short-term servicerelated outcomes (eg, naloxone dispensation, time to MOUD initiation), being retrospective or cross-sectional, or lacking a control group. 21,23,34 The findings of this trial are similar to that of another randomized study conducted by Beaudoin et al 9 that also did not support an effect of PRSSs on post-ED treatment engagement. However, this prior work focused on short-term MOUD linkage, making the POINT study the first randomized trial of such an intervention to consider longer-term overdose outcomes.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These results contribute to the growing body of evidence related to the effectiveness of ED-based PRSS interventions for OUD, with most prior research of similar interventions focusing on relatively short-term servicerelated outcomes (eg, naloxone dispensation, time to MOUD initiation), being retrospective or cross-sectional, or lacking a control group. 21,23,34 The findings of this trial are similar to that of another randomized study conducted by Beaudoin et al 9 that also did not support an effect of PRSSs on post-ED treatment engagement. However, this prior work focused on short-term MOUD linkage, making the POINT study the first randomized trial of such an intervention to consider longer-term overdose outcomes.…”
Section: Discussionsupporting
confidence: 81%
“…18,19 Thus, PRSSs can provide alternative harm reduction and recovery paths for patients who decline treatment or who face greater access barriers. 20,21 Prior research has demonstrated ED-based PRSSs' ability to engage patients and distribute the overdose-reversing drug naloxone. 22,23 However, their capability to improve treatment linkage, including linkage to evidence-based medications for OUD (MOUD; eg, methadone, buprenorphine, and injectable, long-acting naltrexone) or to improve clinical outcomes such as overdose and ED re-presentations have not been fully demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…We had a relatively high attrition rate during the trial which likely resulted in a degree of attrition bias. High drop-out rates are common in both addiction treatment [63,64] and research [62]. The expected drop-out rate was likely compounded by our restriction to distance contact during the pandemic.…”
Section: Limitationsmentioning
confidence: 97%
“…An analysis of a large cohort in a treatment setting found that only 20% of individuals completed a 30-day program [63]. In another analysis of 1,208 patient encounters in an emergency department, PRCs were able to complete at least one follow up with only 23% of individuals [64]. In practice settings, adherence varies significantly and most often ranges between 33%40,65 and 66%.66 Some programs have shown much higher rates of adherence but these are most often in conjunction with much more intensive interventions such as methadone treatment which make them incomparable with PRC services alone [53,67].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, mobile technologies are increasingly studied to improve treatment outcomes for a variety of illnesses, including AUD [ 9 ]. Prior trials that have combined smartphones with peer recovery coaches have included primary care patients with hazardous drinking [ 10 , 11 ] or individuals in the emergency department with opioid use disorder [ 12 ]. However, there are no prior studies that have attempted to leverage technology to increase engagement with peer recovery coaches to specifically improve linkage to care following inpatient alcohol withdrawal management treatment.…”
Section: Introductionmentioning
confidence: 99%